THE LEGAL STANDING & INHERITANCE RIGHTS FOR OUT-OF-WEDLOCK CHILD IN RELATION TO THE CONSTITUTIONAL COURT'S DECISION IN TERMS OF CIVIL INHERITANCE LAW - Arinie Sherlita Cholis (Universitas Muhammadiyah Malang, 2020)
The problems regarding the legal standing of an out-of-wedlock child that demands inheritance rights from both biological parents. The purpose of this thesis are to find out about the legal standing regarding the relationship between out-of-wedlock children and how the inheritance rights of an out-of-wedlock child in the distribution of inheritance by both biological parents are related to the Constitutional Court Decision Number 46/PUU-VIII/2010 in terms of civil inheritance law. The type of research used in this journal is Normative Juridical. The problem approaches used in writing this paper are the Statutory Approach and the Conceptual Approach. The legal material used is primary legal material and secondary legal material. This research of the problem after the Constitutional Court's Decision Number 46/PUU-VIII/2010 can be concluded that the out-of-wedlock child has not only a civil relationship with his mother but also with his biological father if he/she can prove it with science and technology and in inheritance issues, the child out of wedlock in terms of civil law must be recognized by his biological father so that he/she can become an heir, but with the Constitutional Court Decision Number 46/PUU-VIII/2010, the out-of-wedlock child can get not only a share of the inheritance from his mother who is without recognition but also inheritance from his/her biological father if it is proven to have a civil relationship as evidenced by science and technology